Rodas e cortejos de aprender e criar: saberes e fazeres tradicionais na formação de artistas-docentes da cena - Oliveira, Joana Abreu Pereira de (2020)
This research aims to investigate the traditional knowledge and practices in the training processes of artist-teachers in the performing arts. To this end, it is based in an empirical path, seeking reflection on and from practice, which was developed from 2016 to 2019, in the design and implementation of the discipline Manifestações Dramáticas Populares, in the Theater Degree course of Escola de Música e Artes Cênicas from the Federal University of Goiás. Within the scope of this discipline, traditions such as Bumba meu boi, Congada, Tambor de Crioula, Caroço and Cacuriá were experienced, alternating the environment of the university with that of the communities which hold the traditional knowledge and practices visited. Based on the notions of decolonization, ancestry and pluriepistemology, as well as in the debate with masters and teachers, with the students and with authors who are members of traditional communities, the thesis proposes a performance-pedagogical approach methodology for the study of traditional knowledge and practices in Performing Arts pedagogical processes. Some fundamental pedagogical strategies were systematized (Mediated experiences; Meetings with masters; Field experiences; Reports of the lived and references in movement; Performance-pedagogical creations) and ten performance-pedagogical principles were elaborated (Mobilization of the body, Recognition of tradition, Dynamics of tradition, Collectivity, Relationship with ancestry, Sharing of knowledge, Importance of masters, Ability to improvise, Theatricality, Play-sing-dance-tell) to guide the work. It is also noted that the expansion of the university's limits, in the sense of daring to organize time in another way, to carry out learning in other spaces, to establish other hierarchies, was fundamental to the proposed teaching-learning process. In this process, contact with masters and their communities changed pedagogical, aesthetic and, mainly, ethical and social perceptions.